Struggles of Ahmad Shah Durani Against Mughals - Popalzai, Mohammad Zahoor (IJRDO Journal of History & Geography, 2019)
History is a matter of perception. To understand a phenomenal event like Ahmad Shah Durrani s struggle against Mughals, it is imperative to examine various and varying perceptions about it. The study explores the objective of his struggle against Mughals was to consolidate his Kingdom and to establish political hegemony in India as he was quite familiar with the weak Mughal administration of Delhi. Rallying his Afghan tribes and allies, he pushed the Mughals towards the east of India. Within a few years, he occupied Lahore, Multan, Sindh, Kashmir and the sarkar of Sirhind and ruled over his conquered territories in India. The research is comprehensive in nature which is going to answer critical history questions when it comes to the rule of Ahmad Shah Durrani in his conquered territories in India. The study further highlights various perceptions and viewpoints regarding Durrani and his rule in India.